Consistency analysis and conversion model establishment of mini-mental state examination and montreal cognitive assessment in Chinese patients with Alzheimer’s disease - Zhou, Lu; Lin, Zhichuan; Jiao, Bin; Liao, Xinxin; Zhou, Yafang; Li, Hui; Shen, Lu; Weng, Ling (Frontiers in Psychology, 2022)
Background: The Chinese version of the Mini-Mental State Examination (MMSE-C) and the Beijing version of the Montreal Cognitive Assessment (MoCA-BJ) are the most commonly used scales to screen for Alzheimer's disease (AD) among Chinese patients; however, there are still differences in the consistency of the two in different populations and languages. Equivalent conversion of MMSE-C and MoCA-BJ scores is important for meta-analysis. Methods: MMSE-C and MoCA-BJ scoring were performed on the enrolled patients with AD. Consistency analysis of MMSE-C and MoCA-BJ scores of patients in the conversion groups was performed. The circle-arc method was used to convert the MMSE-C scores of the conversion groups into MoCA-BJ scores, and the conversion formula was generated. The MMSE-C data of the verification group was converted into the converted MoCA-BJ according to the formula, and the consistency analysis of the original MoCA-BJ of the verification group and the converted MoCA-BJ was performed to verify the conversion model. Results: The results of the consistency analysis of MMSE-C and MoCA-BJ in group A showed that the correlation coefficients of the total group, high education years subgroup, medium education years subgroup, and low education years subgroup were 0.905 (P<0.001), 0.874 (P<0.001), 0.949 (P< 0.001), and 0.874 (P<0.001), respectively, with high consistency and statistical significance. After applying the circle-arc method for equivalent conversion, the consistency analysis results of the original and the converted MoCA-BJ of the patients in group B of the total group, high education years subgroup, medium education years subgroup, and low education years subgroup were 0.891 (P<0.001), 0.894 (P<0.001), 0.781 (P<0.001), 0.909 (P<0.001), respectively, with high consistency and statistical significance. Conclusion: We established and validated a model of MMSE-C and MoCA-BJ score conversion for Chinese patients with AD by the Circle-arc method. It will useful for multi-centers clinical trials and meta-analysis.